Testing alternative methods of varietal identification using DNA fingerprinting: results of pilot studies in Ghana and Zambia - Maredia, Mywish K.; Reyes, B.A.; Manu-Aduening, J.A.; Dankyi, Ansong A.; Hamazakaza, P.; Muimui, Kennedy K.; Rabbi, Ismail Y.; Kulakow, Peter A.; Parkes, Elizabeth Y.; Abdoulaye, Tahirou; Katungi, E.; Raatz, Bodo (Michigan State University, 2016)
Varietal adoption based on household surveys has mostly relied on farmers’ response to varietal identification. This method can give biased estimates if farmers are unable to identify improved varieties as a group or by name, or give names that do not match with the released variety list. To tackle these potential problems other innovative methods have been suggested that require time and resource intensive data collection such as including follow-up questions in the survey instrument to gather information on varietal traits, visiting the field to observe plant characteristics, or collecting sample materials (i.e., photos, seeds/plant tissues) from the farmers for later verification by experts. However, the accuracy of these different methods for identifying varieties grown by farmers to be able to estimate variety specific adoption is unknown. This paper reports the results of two pilot studies conducted in Ghana and Zambia to test and validate some of these different approaches of collecting variety-specific adoption data against the benchmark of DNA-fingerprinting to determine which method can accurately identify released varieties used by farmers. Results suggest large variations in the estimates of varietal adoption obtained by these different methods compared to DNA fingerprinting results. Results also point to potential challenges of these alternative methods of varietal identification, including DNA fingerprinting in a developing country setting. The implications of these results on future adoption and impact studies are discussed.